Pengaruh Kualitas Produk, Dan Harga Terhadap Keputusan Pembelian Motor Matic Honda Beat (Studi Kasus Pada Dealer Istana Motor Honda Di Bandar Jaya) - Fuadi, Selamet; Sanjaya, Dani Rio (Jurnal Manajemen DIVERSIFIKASI, 2022)
INFLUENCE OF PRODUCT QUALITY, AND PRICE ON MATIC MOTORCYCLE PURCHASE DECISION HONDA BEAT (Case Study at the Honda Motor Palace Dealer in Bandar Jaya) ABSTRACT The development of the automotive industry in Indonesia is very fast and tends to increase every year, in line with the needs and demands of the community for adequate transportation facilities. It is proven by the increasingly crowded city streets and the increasingly congested traffic by motorized vehicles. And followed by the birth and growth of new companies that always try their best to gain and maintain the existing market share. This study aims to determine 1) To find out whether product quality has an effect on purchasing decisions. 2) To find out whether there is an effect on price on purchasing decisions. 3) To find out whether product quality and price affect purchasing decisions. This study uses a quantitative approach. The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. In this study, the population was consumers at the Honda Motor Palace dealer. The sampling technique used was accidental sampling with a total sample of 93 people. Data collection techniques using a questionnaire with a Likert scale. The results showed that: 1) there was a positive effect of product quality on purchasing decisions. 2) there is a positive effect of price on purchasing decisions. 3) there is a positive influence of product quality and price together on purchasing decisions. Keywords: Product Quality, Price And Purchasing Decisions